PENERAPAN ABDOMINAL STRETCHING EXERCISE TERHADAP INTENSITAS NYERI DISMENOREA PADA REMAJA PUTRI - Humaediah Lestari; Windaz Juniarti; Wahyu Cahyono (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Teenagers who menstruate typically experience lower abdominal pain, known as dysmenorrhea. Dysmenorrhea refers to the occurrence of pain during or immediately preceding menstruation. Non-pharmacological interventions include back massage, warm compresses to the lower abdomen, light exercise, and Abdominal Stretching Exercise. This study aims to examine the effect of Abdominal Stretching Exercise on alleviating dysmenorrhea pain intensity. This study applied a quantitative methodology, utilizing a pre- experimental design, specifically a pre-test and post-test with a control group. A purposive sampling technique was employed, with criteria categorized into moderate and mild pain. The total sample size comprised 60 respondents. The results of the study indicated that the t-value for the experimental group was 15.559 with a p-value of 0.000, whereas the t- value for the control group was 7.105 with a p-value of 0.000. The data demonstrated that Abdominal Stretching Exercise was effective in alleviating dysmenorrhea pain intensity.